PSVIII-10 In Vitro Incubation with a Bacillus-Based Direct-fed Microbial Improves Forage Digestibility Parameters. (21st September 2022) - Pan, Liyi; Harper, Karen; Cappellozza, Bruno; Copani, Giuseppe; Queiroz, Oscar
Abstract: Over the years, the use of direct-fed microbials (DFM) has been gaining attention and interest by beef cattle producers and nutritionists, due to health benefits associated with these solutions. Moreover, some bacterial strains currently fed to cattle are also capable of producing and releasing enzymes that might improve nutrient utilization in beef animals. Hence, we hypothesized that the incubation of a Bacillus-based DFM would improve in vitro dry matter (DM) and neutral detergent fiber (NDF) digestibility of ten forage sources (spinifex, buffel grass, Flinders grass, Queensland bluegrass, corn silage, lucerne hay, ryegrass, rhodes grass hay, leucaena, and Mitchell grass hay). Our objective was to evaluate the effects of incubating a Bacillus-based DFM on in vitro forage digestibility. Forage sources were incubated, in triplicate, into the media containing or not Bacillus-based DFM (Bacillus licheniformis and B. subtilis; 3.2 × 10 9 CFU/g; Bovacillus, Chr. Hansen A/S, Horsholm, Denmark) over a 48-h period. The DAISY-II fermentation technique was used with the buffer and nutrient solution described by Goering and Van Soest (1970). The DFM was added to the rumen fluid of treatment groups to simulate the dose of 3 g/animal per day and filter bags were used to isolate 0.5 g of ground forage samples. All data were analyzed using SAS. Inoculation of a Bacillus-based DFM increased overall mean in vitro DM digestibility in 8 out of 10 forage sources with improvements ranging from 6. 1 to 27.3% (P ≤ 0.01). Similarly, mean in vitro NDF digestibility was improved in 8 out of 10 forage types (P ≤ 0.01). In summary, incubation of a Bacillus-based DFM improved in vitro DM and NDF digestibility in forage sources of varying nutritional profile, demonstrating its feasibility to be used in forage-based beef systems.